Peran Pemerintah Desa Dalam Pengembangan Perpustakaan Balai Buntar Untuk Meningkatkan Minat Kunjung Masyarakat Desa Pondok Kelapa Bengkulu Tengah - Lestari, Ayu; Samosir, Fransiska Timoria; Sa’diyah, Lailatus (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2024)
The development of village libraries has had its ups and downs. In this case, Balai Buntar Library, Pondok Kelapa Village, Central Bengkulu, also faced similar problems in its development. The village government has an important role in library development. The purpose of this research is to find out how the role of the village government in the development of Balai Buntar Library to increase the visiting interest of the people of Pondok Kelapa village, Central Bengkulu. This research uses a qualitative approach method on case studies. Data collection techniques used includes observation, interviews, documentation and triangulation. The results of this study indicate that of the six research indicators, namely socialization and promotion of programs, development of facilities and infrastructure, improvement of resources, community involvement, cooperation, and appreciation, as an effort that library staff make in terms of library development to increase community interest in visiting the library has been running and is fully supported by the village government but not maximally. So that the existence of Balai Buntar Library has not been fully felt by the surrounding community considering the number of visitors continues to decline from previous years.